2004
DOI: 10.1111/j.1600-6143.2004.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab as Treatment for Refractory Kidney Transplant Rejection

Abstract: Recent studies have shown that a high density of CD 20+ cells are seen in patients who have steroid-resistant rejection episodes. Rituximab is a high-affinity CD-20 specific antibody that inhibits B-cell proliferation while inducing cellular apoptosis. Thus, it is a rational choice for therapy in transplantation to abrogate B-cell-mediated events. Twenty-seven patients were diagnosed with biopsy-confirmed rejection manifested by thrombotic microangiopathy and/or endothelialitis between 2/99 and 2/02 at our ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
189
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(194 citation statements)
references
References 18 publications
2
189
0
3
Order By: Relevance
“…Some of these antibodymediated rejection episodes are refractory to conventional treatments. Becker et al fi rst reported successful treatment of such a steroid-resistant rejection episode with rituximab (6). Since then a number of case series and reports have been published with regards to success of rituximab in this particular indication (4,6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these antibodymediated rejection episodes are refractory to conventional treatments. Becker et al fi rst reported successful treatment of such a steroid-resistant rejection episode with rituximab (6). Since then a number of case series and reports have been published with regards to success of rituximab in this particular indication (4,6).…”
Section: Discussionmentioning
confidence: 99%
“…Becker et al fi rst reported successful treatment of such a steroid-resistant rejection episode with rituximab (6). Since then a number of case series and reports have been published with regards to success of rituximab in this particular indication (4,6). Rituximab is a chimeric murine/human anti CD 20 antibody which directly inhibits B cell proliferation by antibody-dependent, cell-mediated, and complement-mediated cytotoxicity (7).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, enteroviral infections may not occur with increased frequency in most populations of SOT recipients compared to normal hosts. However, as more biologic agents with B cell depleting properties, such as alemtuzumab and rituximab are being used in patients with solid organ transplant for induction of immunosuppression and therapy for rejection [16,17], it may be that these infections will be encountered more frequently or that more severe infections may occur.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, Becker et al reported that single-dose rituximab reversed steroid-refractory kidney rejection episodes in 24 of 27 patients. 23 Shortly thereafter, Genberg et al showed…”
Section: Anti-b-cell Therapiesmentioning
confidence: 99%